Role of Coffee Caffeine and Chlorogenic Acids Adsorption to Polysaccharides with Impact on Brew Immunomodulation Effects - Passos, Cláudia P. (Foods, 2021)
Coffee brews have High Molecular Weight (HMW) compounds with described immunostimulatory activity, namely polysaccharides and melanoidins. Melanoidins are formed during roasting and are modified during brews technological processing. In addition, brews have Low Molecular Weight (LMW) compounds, namely free chlorogenic acids and caffeine, with well-known anti-inflammatory properties. However, this study shows that both espresso and instant coffee brews did not present immunostimulatory neither anti-inflammatory in vitro activities. It is possible that the simultaneous existence of compounds with antagonistic effects can mitigate their individual effects. To test this hypothesis, an ultrafiltration separation process was applied, studying the behavior of coffee brews’ HMW on retention of LMW compounds. Several ultrafiltration sequential cycles were required to separate retentates from LMW compounds, suggesting their retention. This effect was higher in instant coffee, attributed to its initial higher carbohydrate content when compared to espresso. Separation of HMW and LMW compounds boosted their immunostimulatory (6.2–7.8 µM nitrites) and anti-inflammatory (LPS induced nitrite production decrease by 36–31%) in vitro activities, respectively. As coffee anti-inflammatory compounds are expected to be first absorbed during digestion, a potential in vivo fractionation of LMW and HMW compounds can promote health relevant effects after coffee intake.